Exchange rates and political uncertainty: The Brexit case - Paolo Manasse; Graziano Moramarco; Giulio Trigilia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2020)
This paper studies the impact of political risk on exchange rates. We focus on the Brexit Referendum as it provides a natural experiment where both exchange rate expectations and a time-varying political risk factor can be measured directly. We build a simple portfolio model which predicts that an increase in the Leave probability triggers a depreciation of the British Pound, both on account of exchange rate expectations and of political risk. We estimate the model for multilateral and bilateral British Pound exchange rates. The results confirm the model's main implications. When we extend the analysis to a portfolio model of multiple currencies, we find that the cross-currencies restrictions implied by the theory are not rejected by our system estimation. Moreover, the joint estimates of the multi-currency model in the presence of time-varying political risk premium are in many cases consistent with the Uncovered Interest Parity.
Keywords: F31; F41; G11; G15; 330; Brexit; Exchange Rates; Political Risk; Time-Varying Risk Premium; Uncovered Interest Parity